From Their Point of View: Identifying Socio-Behavioral Profiles of Primary School Pupils Based on Peer Group Perception - Prino, Laura E.; Pasta, Tiziana; Longobardi, Claudio; Marengo, Davide; Settanni, Michele (Frontiers in Psychology, 2018)
Our study adopted a person-based approach with the aim to identify socio-behavioral profiles of primary school students based on peer group perception. The study involved 109 classes and their teachers, from the first three grades of elementary school. The final student sample consisted of 424 children, aged 6-9 years (M = 94.9 months; SD = 9.7), of whom 58.3% were male. We used peer-group nomination to investigate the aspects that are linked to peer group acceptance and perception of classroom behaviors, with reference to academic and relational criteria. We identified and defined six clusters. We validated these clusters by taking into consideration the children’s academic performances and the teacher's perceptions of their relationship with the single students. The identified clusters were related to both of these aspects, and they show predictive value when referring to children's behaviors as ev